INTERSPECIFIC ASSOCIATION OF KAYU LASUN (Dysoxylum alliaceum) AT KETAMBE RESEARCH CENTER, GUNUNG LEUSER NATIONAL PARK DISTRICT ACEH, INDONESIA - Mulyadi Mulyadi; Nursalmi Mahdi; Muslich Hidayat; Rizky Ahadi; Nurdin Amin; Siska Rahayuni (Universitas Islam Negeri Ar-Raniry, 2021)
The Ketambe Research Center is a natural laboratory and one of the nature conservation areas in Indonesia which are rich in biodiversity, located in Gunung Leuser National Park (TNGL). One of the plants found was the Kayu Lasun plant (Dysoxylum alliaceum) which has allelopathic substances. This allelopathic substance can theoretically inhibit the growth, development, and interaction (association) of other plants. The objective was to determine the association of Lasun wood (Dysoxylum alliaceum) with other plants at the Ketambe Research Center. The quadratic method was used as the research design, the station was determined by purposive sampling based on the presence of lasun wood plants (Dysoxylum alliaceum) using non-destructive sampling. Square plots were placed according to the cardinal directions. This study showed the types of plant associations in the area around Lasun wood (Dysoxylum alliaceum) at all observation points found positive and negative types with the degree (strength) of association in the weak category.